Vitamin A, Cancer Treatment and Prevention: The New Role of Cellular Retinol Binding Proteins. (24th March 2015) - Doldo, Elena; Costanza, Gaetana; Agostinelli, Sara; Tarquini, Chiara; Ferlosio, Amedeo; Arcuri, Gaetano; Passeri, Daniela; Scioli, Maria Giovanna; Orlandi, Augusto
Abstract : Retinol and vitamin A derivatives influence cell differentiation, proliferation, and apoptosis and play an important physiologic role in a wide range of biological processes. Retinol is obtained from foods of animal origin. Retinol derivatives are fundamental for vision, while retinoic acid is essential for skin and bone growth. Intracellular retinoid bioavailability is regulated by the presence of specific cytoplasmic retinol and retinoic acid binding proteins (CRBPs and CRABPs). CRBP-1, the most diffuse CRBP isoform, is a small 15 KDa cytosolic protein widely expressed and evolutionarily conserved in many tissues. CRBP-1 acts as chaperone and regulates the uptake, subsequent esterification, and bioavailability of retinol. CRBP-1 plays a major role in wound healing and arterial tissue remodelling processes. In the last years, the role of CRBP-1-related retinoid signalling during cancer progression became object of several studies. CRBP-1 downregulation associates with a more malignant phenotype in breast, ovarian, and nasopharyngeal cancers. Reexpression of CRBP-1 increased retinol sensitivity and reduced viability of ovarian cancer cells in vitro . Further studies are needed to explore new therapeutic strategies aimed at restoring CRBP-1-mediated intracellular retinol trafficking and the meaning of CRBP-1 expression in cancer patients' screening for a more personalized and efficacy retinoid therapy.